A taxonomic study of selected representatives of siphonostomatoida (copepoda) from ostechthyes in coastal waters off Southern Africa - Sebone, Makwena Melita (My University, 2023)
Currently Copepoda consists of 14 600 species of which 2 275 species are members of the Siphonostomatoida. Siphonostomatoida consists of 40 families, with 17 families symbiotic on fish. Sphyriidae has 44 accepted species in eight reported genera, of which four genera infect teleosts and the remaining four infect elasmobranchs. Adult females undergo transformation through loss of locomotory appendages to suit their mesoparasitic lifestyle and develop outgrowths on the cephalothorax or neck for attachment to the host. To date, only 176 marine siphonostomatoid species have been reported from South African waters, with only nine sphyriid species. Sphyriids previously collected from marine bony fish off the east, south and west coasts of southern Africa and preserved in 70% ethanol were studied. Specimens were examined with stereo- and compound microscopes and identified using published literature. Selected specimens were stained in lactic acid with added lignin pink, appendages were dissected and illustrated with the aid of a drawing tube. Selected specimens were also studied through scanning electron microscopy. The examined specimens were identified as species of Sphyrion and Lophoura. Re descriptions were done for all valid Sphyrion species females (S. laevigatum, S. lumpi and S. quadricornis) and new descriptions for the males of S. laevigatum and S. quadricornis. Post-metamorphosis females of Sphyrion species can be differentiated by the shape of cephalothorax, length of the neck in relation to the length of the trunk and the length of posterior processes in relation to the trunk length, while males are mostly very similar. New information is provided regarding the appendages of S. laevigatum and S. quadricornis. The appendages of the three species bear close resemblance to one another. Additionally, an identification key for the post metamorphosis females of Sphyrion species is provided. Re-descriptions were done for five female Lophoura species (L. caparti, L. cornuta, L. cf edwardsi, L. tetraloba and Lophoura sp.) and a new description of the male of L. tetraloba. Differences between young and post-metamorphosis females of L. cf edwardsi and L. tetraloba were observed in the width of the holdfast organ processes and the length of porous peduncle and stalks of the posterior processes which appear to grow with age. The difference between the young and adult male of L. tetraloba lies in the lengths of the cephalothorax in relation to the trunk length and segmentation visible on the trunk of the young male but not adult male. The post-metamorphosis females of Lophoura species can be differentiated by the shape and number of processes on the holdfast organ, in combination with the cephalothorax length in relation to the neck length, neck length in relation to the trunk length, shape of the trunk, and the length and structure of the posterior processes. An identification key was drawn up for all species of the Lophoura post-metamorphosis females. An attempt was made to provide the COI barcodes for all the species of Sphyrion and five species of Lophoura. These would have confirmed the species identification of morphologically variable species e.g. S. laevigatum and S. lumpi and also provide an estimation of the interspecific divergence amongst the different species. Additionally, it would have assisted in distinguishing between L. tetraloba and L. cf edwardsi and provided an estimation of the amount of sequence divergence between the two genera. Unfortunately sequencing of apparently successfully amplified products was unsuccessful probably due to low DNA quality which possibly degraded due to collection methods used for the fish hosts and parasites and prolonged preservation of specimens. This study provides new host records i.e. Coelorinchus simorhynchus, Coelorinchus trunovi and Saurida undosquamis for Sphyrion quadricornis off South Africa which is also a new geographical record. Allocyttus verrucosus, Coelorinchus simorhynchus, Coelorinchus trunovi, Mesovagus antipodum and Ventrifossa nasuta are also new host records for S. lumpi. Additionally, Epigonus denticulatus and Bassanago albescens are new host records for Lophoura caparti and L. cornuta respectively off South Africa, which is a new geographical record for both species. Furthermore, Coelorinchus fasciatus and Lucigadus ori are new host records for Lophoura tetraloba and L. cf edwardsi off South Africa, which is also a new geographic record for both species. Thus, the results of the study improve the current knowledge of the marine siphonostomatoid biodiversity off South Africa as well as their distribution and infected hosts.
Thesis (M.Sc. (Zoology)) -- University of Limpopo , 2023
Keywords: Taxonomic; Copepoda; Siphonostomatoida; Osteichthyes; Copepoda; Siphonostomatoida; Osteichthyes